MODEL EXPERIENTAL LEARNING DALAM MENINGKATKAN PEMAHAMAN KONSEP SISWA KELAS XI PADA MATERİ CAHAYA DAN OPTIK - Wardhana, Farel Razaq; Rahmad, Muhammad; Yennita, Yennita (LPPM UNIVERSITAS PGRI SILAMPARI, 2024)
In physics learning, students are expected to be able to understand physics concepts thoroughly and be able to relate them to the phenomena they encounter. Based on SMAN 6 Pekanbaru, researchers highlighted that educators often find that students have concepts that are different from scientific concepts. So it is necessary to research on understanding concepts with the help of innovative learning models. The aim achieved is to determine the effect of Experiential Learning on increasing class XI students' understanding of concepts in light and optics. Quasi Experiment is the method used with a Posttest-Only Control Design. The results of the posttest understanding of concepts in the experimental class were superior to those in the control class. We can conclude that understanding of concepts in class XI light and optics at SMAN 6 Pekanbaru can be improved through the application of the Experiential Learning model.